Vulnerabilities and Threats to AIS Security Systems - Dola Ramalinda; Agung Raharja (Journal of Computer Science Advancements, 2024)
This research explores vulnerabilities and threats to Accounting Information Systems (AIS) and evaluates effective mitigation measures to address these issues. Using both qualitative and quantitative approaches, this research involved literature studies, surveys, expert interviews, and case analysis to identify and analyze the different types of vulnerabilities and threats faced by AIS. The results showed that human error, software flaws, and system integration complexity are the main sources of vulnerabilities in AIS. The most common threats are cyberattacks, insider threats, and Distributed Denial of Service (DDoS) attacks. The impact of these threats includes financial loss, reputational damage, and significant legal implications.Mitigation strategies identified include the development of robust security policies, the use of cutting-edge security technologies, and the conduct of regular audits and monitoring. The findings emphasize the importance of a layered approach to improving AIS security and reliability. This research provides an in-depth insight into how organizations can identify, evaluate and manage vulnerabilities and threats to their AIS, which is essential for maintaining the integrity, confidentiality and availability of accounting data in an increasingly complex digital age.